Hydrolysis of microcrystalline cellulose isolated from waste seeds of Leucaena leucocephala for glucose production - Husin, Maryam; Rahim, Nurnadiah; Ahmad, Mohd Radzi; Romli, Ahmad Zafir; Ilham, Zul (Penerbit UTM Press, Universiti Teknologi Malaysia, 2019)
The waste seeds of Leucaena leucocephala (LLS) used in this study were unused residues obtained after oil and polysaccharides extraction. The microcrystalline cellulose (MCC) was isolated from LLS by acid treatment. MCC produced was, then, further converted to glucose by using sulphuric acid at 121 °C by varying the acid concentration and reaction time. The sugar composition was analyzed by using the phenol-sulfuric acid method and pre-column derivatization HPLC technique. The yield of glucose ranging from 70–85% could be obtained from MCC hydrolyzates, depending on the hydrolysis factors, which corresponding to around 57-75% of the percentage conversion of MCC to glucose.Cellulose isolated from LLS was, therefore, potentially suitable to be utilized in liquid biofuels and other value-added chemicals such as bioethanol, 5-hydroxymethylfurfural(HMF), and levulinic acid.